PENGARUH INVESTASI, PENGELUARAN PEMERINTAH, TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN DI PROVINSI BALI - Supratiyoningsih, Lufi; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.01.TAHUN.2022DO - 10.24843/EEB.2022.v11.i01.p01, 2022)
This study aims 1) To analyze the effect of investment, government spending and labor on economic growth in Bali Province, 2) To analyze the effect of investment, government spending, labor and economic growth on poverty levels in Bali Province, 3) To analyze the indirect effect of investment, government spending and labor on poverty levels through economic growth in Bali Province. The number of observations in this study was 63 observation points in the period 2013-2019 in 9 districts/cities of Bali Province using panel data. The data analysis technique used in this research is path analysis. The results of this study indicate that 1) Investment has a positive and insignificant effect on economic growth, while government spending and labor have a positive and significant effect on economic growth; 2) Government investment and spending have a negative and insignificant effect on the poverty level, while labor and economic growth have a negative and significant effect on the poverty level; 3) Investment does not indirectly affect the poverty rate through economic growth, while government spending and labor have an indirect effect on the poverty rate through economic growth.